2011
DOI: 10.1002/rcm.5150
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic cyclisation reactions which follow phosphate transfer to carboxylate anion centres for energised [M–H] anions of pTyr‐containing peptides

Abstract: The low-energy negative ion phosphoTyr to C-terminal -CO(2)PO(3)H(2) rearrangement occurs for energised peptide [M-H](-) anions even when there are seven amino acid residues between the pTyr and C-terminal amino acid residues. The rearranged C-terminal -CO(2)PO(2)H(O(-)) group effects characteristic S(N)i cyclisation/cleavage reactions. The most pronounced of these involves the electrophilic central backbone carbon of the penultimate amino acid residue. This reaction is aided by the intermediacy of an H-bonded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…A Tyr phosphate shows the processes [M–H] – → [(M‐H) – – HPO 3 ] and [M–H] – → PO 3 – (Scheme ). The pTyr cleavages are less favourable than the analogous pSer and pThr processes: the loss of HPO 3 and the formation of PO 3 – require +237 and +83 kJ mol –1 at the HF/6‐31+G(d)//AM1 level of theory …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A Tyr phosphate shows the processes [M–H] – → [(M‐H) – – HPO 3 ] and [M–H] – → PO 3 – (Scheme ). The pTyr cleavages are less favourable than the analogous pSer and pThr processes: the loss of HPO 3 and the formation of PO 3 – require +237 and +83 kJ mol –1 at the HF/6‐31+G(d)//AM1 level of theory …”
Section: Methodsmentioning
confidence: 99%
“…Much of the recent work concerning the identification of phosphorylation sites in peptides and proteins by mass spectrometry has been reviewed . Most studies in this area have involved tandem mass spectrometry using positive‐ion mass spectrometry techniques, but there have also been reports of negative‐ion spectra of phospho‐peptides and proteins . For example, the [M–H] – anions of Ser‐ and Thr‐containing phosphates show the processes [M–H] – → [(M‐H) – – H 3 PO 4 ] and [M–H] – → H 2 PO 4 – (Scheme , R = CHO) [ΔG values at the MP2/6‐31++G(d,p)//HF/6‐31++G(d,p) level of theory] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the application of electrospray ionization mass spectrometry (ESI-MS) has been reported to analyze the phosphoryl molecules [4][5][6][7][8][9][10][11]. Interestingly, several phosphoryl group (P O) participated rearrangement reactions were reported in gas phase, such as phosphoTyr to C-terminal CO 2 PO 3 H 2 rearrangement [7], the phosphoryl rearrangement of P N to P O bonds [8,9], methoxyl group migration [10], and carbonyl oxygen migration [11]. It was found that phosphorus involved rearrangement reactions often go through five-membered intermediate easily, but are difficult to form a six-, especial seven-membered * Corresponding authors.…”
Section: Introductionmentioning
confidence: 99%